Sustainable ecotourism in the mangroves "San Pedro" of vice, Sechura – Piura - Charcape Ravelo, Jesús Manuel (2018)
Ecotourism is based on the conservation of nature, ancestral cultures and education; organized in small local businesses, reducing negative impacts to the natural and sociocultural environment, generating economic benefits and jobs for local communities and tourists. Sustainability occurs, if the economic, social and environmental impacts meet the needs of the present, without limiting the possibility of satisfying them, with the same degree of fulfillment and enjoyment in the future. This is possible in the mangroves of "San Pedro" de Vice, with a zoning, trails and carrying capacity tourism.Areas were defined in the mangrove, such as tourist and recreational use, where a path of 1100 meters long and 1.5 meters wide was established, which is equivalent to 1650 m2.The carrying capacity tourism is 795 visitors per day, divided into 10 groups of 12 people separated at a distance of 100 meters; The tour will last 60 minutes, and 7 weekly visits (from Tuesday to Sunday) can be made.